Ndumma Banana Leaf: A Local Lanny Tradition from a Christian Soteriological Perspective - Daniel Wenda; Milinggen Kogoya (Indonesian Journal of Advanced Research, 2026)
This study aims to examine the meaning and role of the Ndumma Banana Leaf tradition in the lives of the Lanny people, explore the salvific values it contains, analyze its relevance from a Christian soteriological perspective, and contribute to the development of contextual theology that respects local Papuan culture. The study uses a qualitative approach with a literature study method. Data were obtained from various scientific sources that discuss Lanny culture, local Papuan traditions, contextual theology, and Christian soteriology. The data were analyzed using content analysis and contextual hermeneutics to examine the relationship between local cultural values and Christian teachings on salvation. The results show that the Ndumma Banana Leaf tradition contains the values of acceptance, reconciliation, sacrifice, solidarity, togetherness, and responsibility for the environment. These values are in harmony with the principles of Christian soteriology that emphasize the restoration of human relations with God, others, and all creation. This study also found that the Ndumma Banana Leaf can be understood as a cultural symbol that functions as a theological bridge in explaining the meaning of salvation contextually to the Lanny people. The novelty of this research lies in its attempt to interpret the Ndumma Banana Leaf tradition not only as a cultural heritage but also as a medium for theological reflection that reconciles the Gospel and local culture without losing their respective identities. These findings reinforce the importance of dialogue between church, culture, and society in the contemporary Papuan context.